ANALISIS EFEKTIVITAS KEMUDAHAN PENGGUNAAN MOBILE BANKING MUAMALAT DIN (DIGITAL ISLAMIC NETWORK) PADA GENERATION Z (ZOOMER) (STUDI KASUS BANK MUAMALAT KCP SERDANG) - Humairah Hajijah; Atika; Nur Ahmadi Bi Rahmani (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2025)
This study aims to evaluate the usability and user satisfaction of the Muamalat DIN Mobile Banking application among Generation Z, a cohort widely recognized as digital natives. The primary focus lies in assessing the effectiveness of the application’s features in addressing the demands of digital Islamic banking transactions. Employing a descriptive qualitative approach, data were gathered through in-depth interviews, field observations, and document analysis. The findings indicate that the application demonstrates a high level of user-friendliness, ensures transaction security, and adheres to the principles of Shariah-compliant finance. Nonetheless, to sustain user engagement and strengthen loyalty among younger generations, continuous enhancement of features and service quality emerges as a strategic imperative